2015
DOI: 10.5194/bg-12-2549-2015
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication mitigation in rivers: 30 years of trends in spatial and seasonal patterns of biogeochemistry of the Loire River (1980–2012)

Abstract: Abstract. Trends and seasonality analysis from 1980 onward and longitudinal distribution, from headwaters to estuary, of chlorophyll a, nitrate and phosphate were investigated in the eutrophic Loire River. The continuous decline of phosphate concentrations which has been recorded since 1991 both in the main river and in the tributaries has led to the conclusion that it was responsible for the significant reduction in phytoplanktonic biomass across the whole river system, although Corbicula spp. clams invaded t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
81
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 63 publications
(84 reference statements)
14
81
0
1
Order By: Relevance
“…High phosphorus concentrations during low flow are commonly interpreted as resulting from undiluted point sources (Withers et al, 2014;Bowes et al, 2014Bowes et al, , 2015Minaudo et al, 2015), and this may lead catchment managers to target point sources as a priority to reduce eutrophication risk during the summer lowflow period. However in the present study, high SRP during low flow was also observed in headwater catchments free of point-source contributions, and this phenomenon was more prominent in the headwater catchments with the presence of riparian hydromorphic soils (US-Agr and US-For).…”
Section: In-stream Processes and Point-source Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…High phosphorus concentrations during low flow are commonly interpreted as resulting from undiluted point sources (Withers et al, 2014;Bowes et al, 2014Bowes et al, , 2015Minaudo et al, 2015), and this may lead catchment managers to target point sources as a priority to reduce eutrophication risk during the summer lowflow period. However in the present study, high SRP during low flow was also observed in headwater catchments free of point-source contributions, and this phenomenon was more prominent in the headwater catchments with the presence of riparian hydromorphic soils (US-Agr and US-For).…”
Section: In-stream Processes and Point-source Contributionsmentioning
confidence: 99%
“…Thus, monitoring headwater catchments was necessary to disentangle both types of processes, as observed downstream export regimes may not describe well the dynamics of landto-stream transfer (Worrall et al, 2012;Minaudo et al, 2015;Temnerud et al, 2016;Baronas et al, 2017). Furthermore, both upstream processes (e.g., summer SRP release) and downstream contributions (e.g., point-source SRP contribution during summer) may lead to the same export regime (e.g., high SRP during low flow); this phenomenon creates epistemic uncertainty, which may lead to equifinality problems when calibrating catchment models to the data (Beven, 2013).…”
Section: Implications For Monitoring and Managementmentioning
confidence: 99%
“…, Minaudo et al. ) and eutrophication (Stoddard et al. ) of lakes and rivers will impact biodiversity and functionality of algae, which are an important carbon source for higher trophic levels (Finlay , Brett et al.…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication, manifested by severe algae blooms, is globally the most pervasive water quality challenge [1][2][3]. It perturbs ecosystem services of the aquatic systems and decreases biodiversity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%